Electrochemical Measurements of Ni / Graphene based Nanohybrids for Electrochemical Energy Storage “ Supercapacitors” - I. Djebablia, O. Guellati, N. Habib, A. Harat, F. Djefaflia, A. Nait-Merzoug, I. Janowska and M. Guerioune (ENP Engineering Science Journal, 2023)
Given the issues related to the use of fossil fuels and water pollution, the development and the application of new smart nanomaterials for supercapacitors and biosensors has become a vital issue for human and industrial societies. Therefore, nanotechnology has given more interest to these areas via micro/nanosystems or nanohybrids characterized by interesting composition, significant porosity and texture at nanoscale. In this work, we have produced electroactive nanohybrids based on in-situ Ni mono-hydroxide few layers Graphene oxide "GO" using a simple and low cost hydrothermal technique under well-studied thermodynamic conditions (120 and 180 °C growth temperature), for performant supercapacitor devices. We have carried out the structural, morphological, textural and optical characterization of these products and consequently we have specified the relationship between their physico-chemical characteristics and their electrochemical properties for ulterior application. Thus, we have carried out various electrochemical measurements through CV tests and we have marked the important electrochemical properties of these Ni/Graphene nanohybrids in two NaOH electrolyte concentrations (0.1 and 1 M) in order to improve the performance of supercapacitors which have become a socio-economic issue with this nanotechnological development. Consequently, these obtained Ni/Graphene nanohybrids have shown a very interesting electrochemical results with specific capacities 1863 and 253 F.g-1 for the case of nanohybrid obtained at 6h/120°C in NaOH aqueous electrolyte with two different concentrations (1 and 0.1M), respectively. However, for a fixed electrolyte concentration of 1M NaOH, both nanohybrids obtained at 120 and 180°C gave specific capacity values around 1863 and 2981 F.g-1, respectively.